Validation study of Malay (Bahasa Melayu) version of the dialectical behavior Therapy- Ways of Coping Checklist (DBT-WCCL) and its psychometric properties - Thong Vie Cheong; Nicholas Tze Ping Pang; Assis Kamu; Noor Melissa Nor Hadi; Helen Benedict Lasimbang; Chong Mun Ho (Bentham Open., 2025)
Dialectical Behavioral Therapy-Ways of Coping Checklist (DBT-WCCL) is widely used to assess coping strategies after a DBT intervention. This study aimed to validate the Malay adaptation of the DBT-WCCL and assess its psychometric properties. A total of 300 bilingual university students participated in the validation process. The DBT-WCCL was translated into Malay using standardized translation and back-translation procedures with expert reviews. Both the English and Malay versions were administered alongside the Mindfulness Attention and Awareness Scale (MAAS) for correlation analysis. The Malay version DBT-WCCL demonstrated reliability comparable to the original version across three subscales, with most items achieving Cronbach's α >0.80. Confirmatory factor analysis showed strong factor loadings (>0.3) and good model fit indices (CFI and TLI > 0.90; RMSEA and SRMR < 0.08). Discussion: The discussion highlights that the Malay version of the DBT-WCCL demonstrates generally strong reliability and validity, particularly for the Blaming Others subscale, though certain items showed weak psychometric performance due to possible cultural mismatches. The Malay version of the DBT-WCCL demonstrated preliminary evidence reliability and validity. However, cultural limitations suggest that a locally adapted version may enhance its future use in Malaysian clinical and research settings.